PENGAWASAN DALAM PEMUNGUTAN RETRIBUSI TERMINAL DI TERMINAL DEPOK DALAM RANGKA MENINGKATKAN PENDAPATAN ASLI DAERAH TAHUN 2020 SAMPAI DENGAN 2022 - Ahmad, Aisyah Noor; Selvi, Selvi (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Terminal levy collection is an important source of income for local goverments, but there are often problems in supervising levy collection, resulting in the target not being achieved. This research uses a descriptive approach which aims to describe the condition of supervision carried out in levy collection at the Depok Terminal. Data collection techniques were carried out through interviews with terminal managements officers, drivers, as well as direct observation in the field. The research results show that supervision of terminal levy collection still experiences various obstacles, namely weakening supervision by direct superiors, lack of technological support, limited number of levy collection officers and the occurrence of fraud when collection levies. However, there are effort to increase supervision, namely by increasing the number of officers, digitalization systems, and strict sanctions for officers who commit fraud.